2005
DOI: 10.1104/pp.104.058032
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Transcription Factor MYB12 Is a Flavonol-Specific Regulator of Phenylpropanoid Biosynthesis

Abstract: Comprehensive functional data on plant R2R3-MYB transcription factors is still scarce compared to the manifold of their occurrence. Here, we identified the Arabidopsis (Arabidopsis thaliana) R2R3-MYB transcription factor MYB12 as a flavonolspecific activator of flavonoid biosynthesis. Transient expression in Arabidopsis protoplasts revealed a high degree of functional similarity between MYB12 and the structurally closely related factor P from maize (Zea mays). Both displayed similar target gene specificity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
614
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 701 publications
(660 citation statements)
references
References 70 publications
19
614
2
1
Order By: Relevance
“…Among the R2R3 MYB, it has been demonstrated that the maize P gene (ZmP) and its Arabidopsis functional homolog MYB12 control the transcriptional activation of the phenylpropanoid biosynthetic genes chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H) and flavonol synthase 1 (FLS1) (Grotewold 2005;Mehrtens et al 2005;Luo et al 2008). Furthermore, it was reported that ZmP as well as MYB12 are up-regulated by UV-B exposure (Casati & Walbot 2005;Oravecz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Among the R2R3 MYB, it has been demonstrated that the maize P gene (ZmP) and its Arabidopsis functional homolog MYB12 control the transcriptional activation of the phenylpropanoid biosynthetic genes chalcone synthase (CHS), chalcone isomerase (CHI), flavonone 3-hydroxylase (F3H) and flavonol synthase 1 (FLS1) (Grotewold 2005;Mehrtens et al 2005;Luo et al 2008). Furthermore, it was reported that ZmP as well as MYB12 are up-regulated by UV-B exposure (Casati & Walbot 2005;Oravecz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The induction of isoflavonoid biosynthesis by elicitation was accompanied by significant decreases in transcript levels of genes encoding members of other R2R3MYB subgroups, including subgroups 4, 7, and 13, which are known to regulate branches of phenylpropanoid metabolism (Jin et al, 2000;Newman et al, 2004;Mehrtens et al, 2005). Members of subgroup 4 are repressors of targeting genes of the GPP (Jin et al, 2000) or monolignol biosynthesis (Legay et al, 2007).…”
Section: Evidence Of Altered Metabolite Flux Through the Phenylpropanmentioning
confidence: 99%
“…Down-regulation of members of subgroups 7 and 13 reflects their roles in positively regulating competing pathway branches. The primary role of genes belonging to subgroup 7 is the control of the genes encoding the enzymes in the flavonoid pathway, including CHS and CHI, required for flavonol biosynthesis in dicot plants and 3-deoxy-flavonoid biosynthesis in monocot plants (Grotewold et al, 1994;Mehrtens et al, 2005). The fact that two genes from this subgroup showed a large decrease in steady-state transcript levels upon elicitation in our experiments and that this was mirrored by down-regulation of CHS1, FLAVANONE 3-HYDROXYLASE (F3H), and FLS suggested that the flavonol branch of the flavonoid pathway competes for the precursors required for isoflavonoid biosynthesis and that the reduced expression of the subgroup 7 TFs likely plays a role in directing the flux of metabolites into the isoflavonoid pathway.…”
Section: Evidence Of Altered Metabolite Flux Through the Phenylpropanmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MYB11, MYB12, MYB111, MYB75/ PAP1, and AtMYBD work as positive regulators whereas MYB-LIKE 2 (MYBL2) functions as a negative regulator. 17,19,[27][28][29][30] Among them, MYB75/PAP1 is a master regulator of the anthocyanin biosynthesis pathway; 19,31 however, direct evidence reflecting whether or not PAP1 can act on the circadian regulation of this biosynthesis pathway is still lacking. 32 Currently, a study has revealed that 2 circadian components NIGHT LIGHT-INDUCIBLE AND CLOCK-REGULATED (LNK) and RVE8 collaborate to control the anthocyanin metabolic pathway.…”
mentioning
confidence: 99%